2021
DOI: 10.1080/15548627.2021.1872188
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin relieves the cataract caused by ablation of Gja8b through stimulating autophagy in zebrafish

Abstract: Macroautophagy/autophagy is known to be important for intracellular quality control in the lens. GJA8 is a major gap junction protein in vertebrate lenses. Mutations in GJA8 cause cataracts in humans. The well-known cataractogenesis mechanism is that mutated GJA8 leads to abnormal assembly of gap junctions, resulting in defects in intercellular communication among lens cells. In this study, we observed that ablation of Gja8b (a homolog of mammalian GJA8) in zebrafish led to severe defects in organelle degradat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 78 publications
(110 reference statements)
1
27
0
Order By: Relevance
“…A heterozygous G-to-A substitution in the exon region of GJA3 gene was detected and resulted in the replacement of Asp with Gly at the N-terminus of Cx46 protein in a Chinese family with congenital nuclear pulverulent and posterior polar cataract (Rees et al, 2000). Another Cx46 variant, R76H, was identified in a large Australian cataract pedigree with zonular pulverulent cataract by using linkage analysis (Ping et al, 2021). Most of these mutations in the Cx46 protein are present in the N-terminal, the first transmembrane, and extracellular domains.…”
Section: Cx46 and Cx50 In Cataract Formation Mutations Of Cx46 And Cx...mentioning
confidence: 99%
See 1 more Smart Citation
“…A heterozygous G-to-A substitution in the exon region of GJA3 gene was detected and resulted in the replacement of Asp with Gly at the N-terminus of Cx46 protein in a Chinese family with congenital nuclear pulverulent and posterior polar cataract (Rees et al, 2000). Another Cx46 variant, R76H, was identified in a large Australian cataract pedigree with zonular pulverulent cataract by using linkage analysis (Ping et al, 2021). Most of these mutations in the Cx46 protein are present in the N-terminal, the first transmembrane, and extracellular domains.…”
Section: Cx46 and Cx50 In Cataract Formation Mutations Of Cx46 And Cx...mentioning
confidence: 99%
“…Every single connexin protein consists of four transmembrane domains (T1-T4), two extracellular loops (EL1, EL2) with a cytoplasmic loop (IL), and cytoplasmic N-terminal and C-terminal components (Figueroa et al, 2019;Mese et al, 2007;Sánchez et al, 2019). Three connexins presented in the lens are α1 (Cx43), α3 (Cx46), and α8 (Cx50), which are encoded by three genes: Gja1, Gja3, and Gja8, respectively (Yue et al, 2021;Ping et al, 2021). In the layer of lens epithelial cells, abundant expression of Cx43 could be detected, whereas Cx46 is exclusively present in the lens fiber cell, where its expression corresponds with fiber cell differentiation, and Cx50 is widely expressed in both lens epithelial and fiber cells (Figure 1) (Paul et al, 1991;Delvaeye et al, 2018;Ceroni et al, 2019;Tong et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last two decades, many new surgery technologies dramatically advanced cataract surgical treatments (9-13). Besides, various molecular studies about cataractogenesis enriched the cataract formation mechanism and provided novel applications for non-surgical treatments, including breakthroughs in possible pharmacological treatments (14)(15)(16)(17)(18).…”
Section: Cataractmentioning
confidence: 99%
“…However, the precise effect of autophagy on the lens is an open area of inquiry. Our previous research had found that rapamycin (rapa), an activator of autophagy, effectively rescued lens opacities in GJA8 −/− zebrafish [ 10 ]. Conversely, hyperactive autophagy may result in cell viability deprivation and death [ 11 ].…”
Section: Introductionmentioning
confidence: 99%